Development of Silvicultural Management Models for Gmelina arborea Roxb. Stands in Area J4, Omo Forest Reserve, Nigeria (2021)
Plantation establishment of fast-growing species such as Gmelina arborea has been suggested as a quick fix to the perennial problem, especially in Omo Forest Reserve. Management models have been identified as tools for sustainable management and monitoring of Gmelina plantation. Hence, silvicultural management models were developed for sustainable management of Gmelina plantation in Omo Forest Reserve. Nine Gmelina arborea age series (34, 32, 30, 26, 24, 22, 20, 18 and 16 years old) stands were purposively selected in Area J4 of Omo forest reserve. A total of Sixty-five temporary sample plots were demarcated proportionate to size across the age series. In each plot, diameter at breast height and stem height were measured to estimate stand basal area and volume. Silvicultural management models were developed to estimate the optimum rotation volume, area and number of stock to harvest using the linear programme option of the R package to obtain the solutions of the planning model for 20 years at 5 years period. It was observed that the mean tree dbh and stem height ranges from 21.50 to 70.61 cm and 16.08 to 24.98 m respectively. The mean basal area and stem volume had the respective values which range from 33.31 to 413.78 m2/ha and 423.19 to 8413.52 m3/ha. At the individual tree level, mean annual growth is attained at 27 years. This represents the optimal rotation age of any Gmelina arborea stand in Omo forest reserve. If selective logging is applied for timber purpose, a rotation age of 27 years will be the appropriate rotation age. However, if clear-felling is opted for, the appropriate rotation age will be 25 years. The logging plan that optimizes volume in terms of area cut in each stand and period revealed that in 16 years old stands, whole logging will take place only during the last period of the plan, removing 5.00ha. The respective area to be cut during the 1st, 2nd, 3rd and 4th periods are 451.70ha, 517.50ha, 250.80ha and 140.00ha. The harvesting schedules obtained in this study have shown that the management planning model provides rational and practicable results.